Clinical features and antimicrobial resistance profiles of important Enterobacteriaceae pathogens in Guangzhou representative of Southern China, 2001–2015. (June 2017) - Xie, Jinhong; Peters, Brian M.; Li, Bing; Li, Lin; Yu, Guangchao; Xu, Zhenbo; Shirtliff, Mark E.
Abstract: Object: This surveillance aimed to investigate the antimicrobial resistance profiles of Enterobacteriaceae pathogens in Southern China during 2001–2015. Methods: A total of 6858 Enterobacteriaceae isolates were collected, including 4276 E. coli, 1992 K. pneumoniae and 590 Enterobacter spp. Disk diffusion method and minimum inhibitory concentrations method were used for susceptibility testing, with results interpreted by the CLSI (2015). Results: Urinary tract remained the dominant isolated site among E. coli (49.88%), whereas 53.26% K. pneumoniae and 45.25% Enterobacter spp. were from Sputum. The carbapenems maintained the highest antimicrobial activity (resistance rates <15%), followed by piperacillin-tazobactam and amikacin. Gentle increases were obtained in carbapenems-resistant K. pneumoniae and Enterobacter spp. (eg. from 4.5% to 11.2% and 3.2% to 14.5% in imipenem, repestively). The third-generation cephalosporins showed high and stable resistance among Enterobacteriaceae pathogens during the studied period, with ceftazidime as the most active third-generation cephalosporin against Enterobacteriaceae . Isolates from ICU department showed higher or similar resistance rates among Enterobacteriaceae pathogens compared to other wards. Conclusion: Carbapenems are the most potent antibiotic agents against Enterobacteriaceae pathogens. Due to the complicated susceptibility profiles, prescribing guidelines should be based on the knowledge of antibiogram of pathogens. Highlights: Urinary tract, sputum and bloodstream are the frequently isolated sites. Carbapenems maintained the most potent antimicrobial activity. Increases were found in carbapenems-resistant K. pneumoniae and Enterobacter spp. Isolates showed higher or similar resistance in ICU ward than other wards.